Utilisation of Waste Sludge from Drinking Water Treatment as a Filler Material in Hot Mix Asphalt - Kahveci, Tuna Eyup; Ozen, Halit (MDPI, 2024)
This research investigated the suitability of using sludge from the treatment of drinking water in hot mix asphalt (HMA) as a filler material. The storage and environmental impact of sludge is an enormous problem, especially for countries with large populations. Two different types of sludges, ferric chloride (FC) and aluminium sulphate (AS), were used as a filler material in HMA. The Hamburg Wheel Tracking (HWT) test, which correlates with rutting, and the Indirect Tensile Strength (ITS) test, which indicates the moisture sensitivity of HMA, were carried out at the optimum bitumen content of the mixes to investigate the usability of sludge in HMA. The test results indicate the usability of FC and AS in HMA compared to the reference mixes. However, the AS type of sludge has better rutting resistance than the FC type. Although the results support the usability of both sludges in HMA, it should be noted that the increased cost of the mix containing sludges due to the combustion process and the increased bitumen content during application should be considered.
Keywords: sludge; HMA; waste; filler; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics